Sedative and anxiolytic effects of Capparis sicula Duhamel: in vivo and in silico approaches with phytochemical profiling - Karpuz Ağören, Büşra; Küpeli Akkol, Esra; Çelik, Ismail; Sobarzo-Sánchez, Eduardo (Frontiers in Pharmacology, 2024)
The World Health Organization reports that 30% of adults worldwide suffer from insomnia, while 10% of people worldwide suffer with various forms of anxiety. The significant negative effects of conventional medications used to treat anxiety and insomnia, such as abuse, addiction, amnesia, and cognitive and sexual dysfunction, have led to an increased preference for naturally derived substances with fewer side effects. Accordingly, in this study, the sedative and anxiolytic effects of n-hexane, ethyl acetate (EtOAc), methanol (MeOH) and water extracts of the aerial parts of Capparis sicula Duhamel., which is used for sedative purposes in folk medicine, were evaluated. To evaluate the sedative and anxiolytic effects of each extract, bioassay systems were used including traction and hole-board tests. The MeOH extract of C. sicula was the most active extract on in vivo traction and hole-board tests compared to Diazepam. From the MeOH extract, major components were isolated, and their structures were identified as three flavonoid glycosides [rutin (1), quercetin-3-O-glucoside (2), and quercetin 3-O-rhamnoside (3)] using spectral techniques. The most abundant component was determined to be rutin, comprising 8 mg/100 mg dry extract in MeOH extract and 76.7 mg/100 mg dry fraction in fraction C using HPLC. The molecular docking studies evaluated the interaction of isolated flavonoid glycosides with the interaction energies and protein-ligand interaction details of the anxiety-related receptors GABAA and GABAB. For the GABAA receptor, quercetin-3-Oglucoside demonstrated the highest docking score. Quercetin-3-O-rhamnoside and rutin also show promising interactions, particularly with the GABAB receptor, highlighting their potential as modulators of these receptors. In conclusion, the use of C. sicula for sedative purposes in folk medicine has been confirmed for the first time by in vivo studies, and its possible active compounds and sedative-anxiolytic mechanism have been determined through phytochemical and in silico studies.